(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article examines the role of social media platforms as tools for enhancing speaking proficiency among university students. The shift toward digital education has opened new avenues for language learning, where platforms like Facebook Live, Clubhouse, and YouTube serve as informal environments for practicing oral communication. This study emphasizes the potential of interactive content, online discussions, and collaborative digital tasks in promoting fluency, pronunciation, and confidence in speaking.